Effectiveness of compassion-based online therapy on suicidal thoughts and pain catastrophizing in female patients with multiple sclerosis in the relapsing–remitting phase - Mohamadpour, Fahimeh (Frontiers in Psychology, 2023)
According to research, multiple sclerosis is related to suicidal thoughts and pain catastrophizing as psycho-pathological variables, and on the other hand, compassion-based treatment can reduce mental disorders by targeting dimensions such as self-compassion. Also, since this disease is progressive and over time can cause movement restrictions in these people, online psychotherapy can be a better option for these people. So, the purpose of this study was to investigate the effectiveness of online compassion therapy on suicidal thoughts and pain catastrophizing in female patients with multiple sclerosis.The current research was applied and quasi-experimental in a pre-test-post-test manner with a control group. The research sample consisted of 30 patients with multiple sclerosis living in Shiraz in 2019, who were randomly divided into two 15-person experimental and control groups. The participants were tested on scales of suicidal thoughts and pain catastrophizing, and the treatment plan based on compassion therapy was presented to the participants of the experimental group in 8 two-hour sessions online. The control group was placed on the waiting list until the completion of the treatment sessions and the post-test implementation, and after the post-test implementation, they received the treatment. Control variables in this study included gender and disease phase. Then, their scores were measured, after completing the treatment, and a three-month follow-up period. Descriptive statistics and covariance test were used to analyze the data.Results: Patients showed a clear improvement in the severity of symptoms in both variables. So that the scores of suicidal thoughts and pain catastrophizing in the experimental group after receiving the treatment, as well as after a three-month follow-up period, were significantly reduced (p<0.001).Confirming the effectiveness of online therapy based on compassion on improving psychological outcomes in these patients, as an effective and online treatment method, is a clear step towards continuing the implementation of psychological interventions and paying attention to the dimension of mental health in this group of people.